2017
DOI: 10.1021/jacs.7b03846
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally Resolved, Functional Super-Resolution Microscopy Reveals Nanoscale Compositional Heterogeneity in Live-Cell Membranes

Abstract: By recording the full fluorescence spectra and super-resolved positions of ∼10 individual polarity-sensing solvatochromic molecules, we reveal compositional heterogeneity in the membranes of live mammalian cells with single-molecule sensitivity and ∼30 nm spatial resolution. This allowed us to unveil distinct polarity characteristics of the plasma membrane and the membranes of nanoscale intracellular organelles, a result we found to be due to differences in cholesterol levels. Within the plasma membrane, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(235 citation statements)
references
References 39 publications
7
227
0
1
Order By: Relevance
“…35 Moreover, coupling this type of multifunctional probe with super-resolution spectroscopy will provide a powerful tool for cell characterization. 36 …”
Section: Mitochondria Morphology Monitoring With the Mmp In Hela Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Moreover, coupling this type of multifunctional probe with super-resolution spectroscopy will provide a powerful tool for cell characterization. 36 …”
Section: Mitochondria Morphology Monitoring With the Mmp In Hela Cellsmentioning
confidence: 99%
“…[35] Moreover,coupling this type of multifunctional probe with super-resolution spectroscopy will provide apowerful tool for cell characterization. [36] Figure 6. A) Time course monitoring of morphology changes:C ells are stained with 10 mm MMP in the initial state (red) and two images were recorded after 10 min and 20 min for control, then 10 mgmL À1 nystatin was added and the images were recorded after each 5min (green).…”
Section: Communicationsmentioning
confidence: 99%
“…S1a). Lipid domains are thought to be sub-100 nm diameter structures, may include protein interactions 24 , but even with super-resolution imaging techniques such as direct stochastic optical reconstruction microscopy (dSTORM) and stimulated emission depletion (STED) [25][26][27][28] their exact structure remains controversial 29,30 . We previously used dSTORM to image livespontaneous and chemical disruption of GM1 domains in muscle cells 5 leading us to asked if force induced disruption could directly be measured with imaging.…”
Section: Mechanical Disruption Of Lipid Rafts In Muscles Cellsmentioning
confidence: 99%
“…After shearing, cells were fixed, stained, and imaged identically to static samples with dSTORM. (b) Recent research has shown variability in the detection of domains in cells based on technique and labeling molecules 29,64,65 . Because of its pentavalent nature, CTxB has been suggested to induce lipid rafts post-fixation due to the idea that lipids remain mobile after fixation.…”
Section: Supplemental Figuresmentioning
confidence: 99%
“…Zhang et al demonstrated imaging four molecular species simultaneously with a single laser and filter set by spreading fluorescence emission spectra across camera pixels and finding the spectral mean (Figure 2d; Zhang, Kenny, Hauser, Li, & Xu, 2015). This can be used to monitor the responses of single-molecules to their local environment (Moon et al, 2017) by using fluorophores that are sensitive to pH, ion concentration, or polarity. Machine learning or deep-learning approaches for single-molecule analysis will provide more information on dynamics (Matsunaga & Sugita, 2018), spectral data and three-dimensional (3D) locations (T. Kim, Moon, & Xu, 2018).…”
Section: High-throughput and High-content Single-molecule Assaymentioning
confidence: 99%